Gastric emptying of hexose sugars: role of osmolality, molecular structure and the CCK1 receptor - Little, T. J.; Gopinath, A.; Patel, E.; Mcglone, A.; Lassman, D. J.; D’amato, M.; Mclaughlin, J. T.; Thompson, D. G. (Neurogastroenterology and motility, 2010)
Background  It is widely reported that hexose sugars slow gastric emptying (GE) via osmoreceptor stimulation but this remains uncertain. We evaluated the effects of a panel of hexoses of differing molecular structure, assessing the effects of osmolality, intra‐individual reproducibility and the role of the CCK1 receptor, in the regulation of GE by hexoses. Methods  Thirty one healthy non‐obese male and female subjects were studied in a series of protocols, using a 13C‐acetate breath test to evaluate GE of varying concentrations of glucose, galactose, fructose and tagatose, with water, NaCl and lactulose as controls. GE was further evaluated following the administration of a CCK1 receptor antagonist. Three subjects underwent repeated studies to evaluate intra‐individual reproducibility. Key Results  At 250 mOsmol, a hexose‐specific effect was apparent: tagatose slowed GE more potently than water, glucose and fructose (P < 0.05). Fructose (P < 0.05) also slowed GE, but with substantial inter‐, but not intra‐, individual differences. As osmolality increased further the hexose‐specific differences were lost. At 500 mOsmol, all hexoses slowed GE compared with water (P < 0.05), whereas lactulose and saline did not. The slowing of GE by hexose sugars appeared to be CCK1 receptor‐dependent. Conclusions & Inferences  The effects of hexose sugars on GE appear related to their molecular structure rather than osmolality per se, and are, at least in part, CCK1 receptor‐dependent.